Examining Social Insurance Perceptions and Attitudes among Zimbabwean Informal Sector Workers: A Study on Providing Social Protection to the Disenfranchised - Bronson Mutanda; Bomi Cyril Nomlala (TIJAB (The International Journal of Applied Business))
Background: Given the rate at which the labour force in Zimbabwe's informal sector continues to evolve, steps need to be taken to promote a culture where employees contribute towards their social insurance. Social insurance is significant since it helps informal sector workers to prepare for life's predictable and unpredictable events, such as retirement, unemployment, old age, incapacity, death and health challenges.